Renewable energy consumption, institutional quality and life expectancy in EU countries: a cointegration analysis - Anca-Florentina Vatamanu; Mihaela Onofrei; Elena Cigu; Florin Oprea (Energy, Sustainability and Society)
Abstract Background Although some socioeconomic, environmental, and political factors could impact life expectancy, the economic literature loses sight of the relationship between the widespread adoption of renewable energy technologies and their potential effect on global life expectancy. An insightful analysis of the socio-economic and environmental benefits associated with renewable sources forms the foundation for investigating the broader implications for public health and well-being. Using panel data from 27 European countries over the period 2000–2020, this study examines the effects of renewable energy consumption on human life expectancy as well as how institutional quality and investment in renewable energy projects might promote better health outcomes. Methods The methodological approach is carefully selected to address salient estimation issues and includes a qualitative sequential methodology involving empiric analysis that provides coherence and viability for our study, but also quantitative methods, including factor analysis, panel fully modified least squares (FMOLS), unit root tests, and cointegration techniques. Results We find that renewable energy consumption and institutional quality can improve life expectancy in EU countries. Furthermore, the empirical evidence indicates that sustaining longevity as a new government strategy requires strong institutional quality, capable of influencing the status of renewable energy and promoting long-term sustainability. Conclusions Our findings bear essential policy implications regarding sustaining longevity as new government strategies and exploring the scale of the target to increase healthy life expectancy. The entire EU health policy and the government's recommitment to narrowing the gap in healthy life expectancy should be focused on improving institutional quality and reducing carbon emissions through promoting projects capable of increasing renewable energy consumption. The results suggest that, on average, a 1% change in renewable energy consumption leads to a 0.331 change in life expectancy, and a 1% change in institutional quality leads to a 0.316 change in life expectancy.